2012
DOI: 10.1159/000338940
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Based Study of Fish Allergy in the Philippines, Singapore and Thailand

Abstract: Background: Fish allergy is the third most common food allergy after milk and egg in parts of Europe, but there is little data about prevalence in South East Asia where it is an important part of regular diets. Objective: We aimed to obtain an estimate of the population prevalence of fish allergy among older children in the Philippines, Singapore and Thailand. Methods: The population prevalence of fish allergy in 14- to 16-year-old children in the 3 countries was evaluated using a structured written questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 47 publications
3
45
1
1
Order By: Relevance
“…Comparing with other Southeast Asian countries, our prevalence rate is similar to that of Thailand (0.29% based on convincing history). (12) The low prevalence in some countries was initially thought to be associated with early introduction of fish to the diet as compared to the West. (32) However, in Connet et al's study, the rate of fish allergy in the Philippines, where fish is similarly introduced to the diet at an early age, was found to be surprisingly high at 2.29%.…”
Section: Fishmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparing with other Southeast Asian countries, our prevalence rate is similar to that of Thailand (0.29% based on convincing history). (12) The low prevalence in some countries was initially thought to be associated with early introduction of fish to the diet as compared to the West. (32) However, in Connet et al's study, the rate of fish allergy in the Philippines, where fish is similarly introduced to the diet at an early age, was found to be surprisingly high at 2.29%.…”
Section: Fishmentioning
confidence: 99%
“…(32) However, in Connet et al's study, the rate of fish allergy in the Philippines, where fish is similarly introduced to the diet at an early age, was found to be surprisingly high at 2.29%. (12) In addition, the allergic profile of the Filipino group demonstrated a late-onset-type of fish allergy, unlike in Singapore where fish allergy usually occurs in the first year of life. (33) It was proposed by the authors that this entity in the Philippines could be due to differences in fish preparation methods, with the high availability of dried and salted fish as opposed to cooked fish, possibly promoting immunogenicity.…”
Section: Fishmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher rates of self-reported allergic reactions were observed in some Asian countries, both for adults (24.5 %; China) (Sai et al, 2011) and children (8.7 % and 11.6 %, respectively; Philippines) (Connett et al, 2012). However, the only study which used OFC to confirm diagnosis reported a prevalence of clinical allergy to crab and shrimp of 0.2 % and 0.9 %, respectively, among three-to seven-year-olds in Thailand (Lao-araya and Trakultivakorn, 2011).…”
Section: Outside Europementioning
confidence: 96%
“…In children from Spain, fish allergy starts in the second year of life and is the third most prevalent food allergy after egg and milk [48]. A recent population-based study in southeast Asia in children 14e16 years old has shown a prevalence of fish allergy of 2.29% in the Philippines, whereas in Singapore and Thailand it is 10 times lower [49].…”
Section: Fishmentioning
confidence: 99%